Thinned-Young Apple Polyphenols Inhibit Halitosis-Related Bacteria Through Damage to the Cell Membrane - Liu, Ting; Shen, Hailiang; Wang, Furong; Zhou, Xueru; Zhao, Pengtao; Yang, Yali; Guo, Yurong (Frontiers in Microbiology, 2022)
The thinned-young apple is by-product and generally discarded in orchard during the fruit thinning. The polyphenol content of thinned-young apple is about 10 times more than that of ripe apples. In our study, the antibacterial effect of thinned-young apple polyphenols (YAP) on the halitosis-related bacteria including Porphyromonas gingivalis, Prevotella intermedius and Fusobacterium nucleatum was investigated. The minimum inhibitory concentration of YAP against P. gingivalis, P. intermedia and F. nucleatum was 8.0 mg/ml, 8.0 mg/ml and 12.0 mg/ml, while the minimum bactericidal concentration was 10.0 mg/ml, 10.0 mg/ml and 14.0 mg/ml, respectively. The scanning electron microscopy and transmission electron microscopy analysis showed that after YAP treatment, the membrane surface of halitosis-related bacterial cells was coarse and the cell wall and cell membrane were separated and eventually ruptured. The flow cytometry was used to determine the integrity of cells membrane, indicating that more cells membrane integrity was destroyed with the increases of YAP concentration treatment. The release of protein and nucleic acid into the cell suspension significantly increased and the membrane potential reduced after the YAP treatment. This research illustrates the antibacterial mechanism of YAP against halitosis-related bacteria and provides a scientific basis of utilizing the polyphenols from the discarded thinned-young apples.